“Enhancing Students’ Creative Thinking through Visual Arts in School and University Education” - Aslonova Shaxnoza Islom qizi, (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: This article explores the role of visua l arts in enhancing students’ creative thinking and problem-solving skills in school and university education. It emphasizes how early exposure to artistic techniques in schools forms a foundation for advanced projects and independent creative work in higher education. The study highlights the importance of integrating visual arts across educational levels to foster cognitive, aesthetic, and professional development in students.